Governing network neutrality: Public perception and policy capacity - Donghee Shin (International Telecommunications Society (ITS), 2013)
Beyond technical matters, the network neutrality debate is closely tied to social, political, and economic debate over networks and the duties and the rights of various stakeholders. The study contextualizes the issue in terms of policy, innovation, values, and the society of Korean context. Focusing on user perspective, it analyzes the policy effectiveness of current network neutrality by analyzing user perception. A model is proposed to empirically test the policy effectiveness by incorporating factors representing network neutrality. The factors are drawn from the belief of people's perceived concepts on network neutrality. The findings show that while competition and regulation are the two main factors constituting network neutrality, both factors influence the formation of attitude toward policy effectiveness differently. Policy and managerial implications are discussed based on the model. Overall, this study provides in-depth analysis and heuristic data on the user drivers, industry dynamics, and policy implication within the network neutrality ecosystem.
Keywords: 330; Network neutrality; Policy capacity; Korea; User-centered policy analysis